KOMITMEN MANAJEMEN DAN KOMUNIKASI KESELAMATAN KESEHATAN KERJA (K3) DI PROYEK BANYU URIP BLOK CEPU - BOJONEGORO - Sudargo, Sudargo (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2017)
AbstractÂ This research is conducted in purpose to find & analyze the influence of organization communication climate, management commitment, level of knowledge & Safety Security Health & Environment awareness exposure towards local non skilled construction workers' (short service workers) incident prevention behavior in Banyu Urip Project Bojonegoro Regency, East Java Indonesia.The research type utilized is explanative which correlates or attempting to find causal impact of two or more concepts (variables) which will be analyzed. The research population is local non-skilled construction workers (short service workers) in Banyu Urip Project Bojonegoro. Research sample covering 215 respondents, data analysis in this research utilizing multiple linier regression to knowledge the influence of two independent variable towards one dependent variable.Research results shows that the organization communication climate (X1), Management Commitment (X2), Level of Knowledge (X3), Campaign Exposure & SSHE Communication (X4) has a signivicant influence on accident prevention (Y) contribute towards incident prevention behavior amount 77.3%, while the rest amount 22.7% is influenced by another factors which is not covered in this research. Â Keywords: Communication, Organization, Management, SSHE, incident prevention behavior.